POLA ASUH DEMOKRATIS DAN MOTIVASI BELAJAR SISWA SMA DI TENTENA POSO PADA MASA PANDEMI COVID-19POLA ASUH DEMOKRATIS DAN MOTIVASI BELAJAR SISWA SMA DI TENTENA POSO PADA MASA PANDEMI COVID-19 - Chintia Kurniasih Basompe; Christiana Hari Soetjiningsih (Bajang Institute, 2023)
The purpose of this stuy was to determine the relationship between democratic parenting and student learning motivation during the Covid-19 pandemic. The participants in this study were students of XII high school in the city of Tentena, Poso Regency, Central Sulawesi, which collected 32 students. The data was collected using a scale of democratic parenting and learning motivation. Data analysis used the product moment correlation method from Pearson. The results showed a significant relationship between democratic parenting and learning motivation in high school students during the Covid-19 pandemic with a value of r = 0,117 and significance = 0,262 (p < 0.05), so it can be said that no there relationship between parenting democratic method applied by parents with student learning motivation.